2016
DOI: 10.1038/srep20386
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the cause of unexplained radiocaesium contamination of brown rice in Fukushima in 2013 using autoradiography and gamma-ray spectrometry

Abstract: The Great East Japan Earthquake on 11 March 2011, caused the release of radioactive materials from the Fukushima Daiichi Nuclear Power Plant (FDNPP), contaminating eastern Japan, particularly in part of Fukushima Prefecture. In 2012 and 2014, the radiocaesium concentration in brown rice did not exceed regulatory levels in Minamisoma City, Fukushima. However, in 2013, some radiocaesium concentrations in brown rice exceeded regulatory levels. In this work, autoradiograms showed that high radioactivity was presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Radio-Cs can be discharged into the environment in the form of aerosol, soluble aqueous solution, or as part of sparingly soluble particles. Significant amounts of Cs were released into the environment during the 1986 Chernobyl (132 PBq) and the 2011 Fukushima Daiichi nuclear power plant accidents (32 PBq). Atmospheric release of radio-Cs aerosols results in plumes of radio-Cs, which are distributed by air-mass movements. Radio-Cs in the plumes is subsequently brought to the ground by wet deposition via precipitation or dry deposition. , Since radio-Cs has a high affinity for clay minerals, it often undergoes sorption to clayey soil particles. , In addition, plants can uptake Cs from air or water, , introducing radio-Cs into the biosphere, which dominates dose in the impacted regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radio-Cs can be discharged into the environment in the form of aerosol, soluble aqueous solution, or as part of sparingly soluble particles. Significant amounts of Cs were released into the environment during the 1986 Chernobyl (132 PBq) and the 2011 Fukushima Daiichi nuclear power plant accidents (32 PBq). Atmospheric release of radio-Cs aerosols results in plumes of radio-Cs, which are distributed by air-mass movements. Radio-Cs in the plumes is subsequently brought to the ground by wet deposition via precipitation or dry deposition. , Since radio-Cs has a high affinity for clay minerals, it often undergoes sorption to clayey soil particles. , In addition, plants can uptake Cs from air or water, , introducing radio-Cs into the biosphere, which dominates dose in the impacted regions.…”
Section: Introductionmentioning
confidence: 99%
“…Current methods used for the detection of radio-Cs in environmental samples include γ spectroscopy and autoradiography. γ spectroscopy is routinely used for the measurement of bulk radio-Cs activity concentrations. , Use of the peak energies at 604.7 keV (Cs-134) and 661.7 keV (Cs-137) also enables accurate measurement of Cs-134/Cs-137 isotopic ratios, which can be used to identify the origin of Cs releases . Autoradiography is an imaging technique that provides high-resolution two-dimensional images of radioactive emissions from a sample.…”
Section: Introductionmentioning
confidence: 99%
“…The high-dose-rate alarm was activated on August 19 within the premises of FDNPP associated with the debris removal operation. Matsunami et al (2016) related the radiocesium contamination of brown rice in Fukushima in 2013 to this operation, whereas MAFF (2015) denied any association. The NRA estimated the 137 Cs emission rate during the debris removal operation as 6.7 × 10 10 Bq h −1 and the cumulative amount as 1.1 × 10 11 Bq (NRA, 2014).…”
Section: Possible Source Of Sporadic Peak Eventsmentioning
confidence: 99%
“…Autoradiography analyses of contaminated rice husks and blades revealed that radioactive materials were not evenly distributed on rice tissues, and, therefore, part of the radiocesium was not likely absorbed from soil through root. In this particular case in 2013, adhesion of airborne radioactive materials on rice plants was the most probable cause of contamination (Matsunami et al 2016), though the source of the airborne radioactive materials was not identified (MAFF 2015a). In 2014, brown rice harvested in Minami-soma city did not exceed 100 Bq kg −1 (MAFF 2015b).…”
Section: Ricementioning
confidence: 98%